2010
DOI: 10.1136/oem.2009.052704
|View full text |Cite
|
Sign up to set email alerts
|

Long-term air pollution exposure and risk factors for cardiovascular diseases among the elderly in Taiwan

Abstract: Changes in blood pressure, blood lipids, blood sugar and haematological markers of inflammation are associated with long-term exposure to ambient air pollutants. This might provide a link between air pollution and atherosclerotic cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
212
10
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(240 citation statements)
references
References 39 publications
12
212
10
6
Order By: Relevance
“…In other mechanistic epidemiology studies, NO 2 was associated with elevated blood pressure, total cholesterol, fasting glucose, glycosylated haemoglobin and IL-6 in a crosssectional study, but this was not maintained after adjustment for other pollutants (Chuang et al, 2011). NO 2 exposure during pregnancy increased CD-8 + T cells in cord blood.…”
Section: Mechanistic Epidemiology Studiesmentioning
confidence: 70%
“…In other mechanistic epidemiology studies, NO 2 was associated with elevated blood pressure, total cholesterol, fasting glucose, glycosylated haemoglobin and IL-6 in a crosssectional study, but this was not maintained after adjustment for other pollutants (Chuang et al, 2011). NO 2 exposure during pregnancy increased CD-8 + T cells in cord blood.…”
Section: Mechanistic Epidemiology Studiesmentioning
confidence: 70%
“…In the study done by Cesaroni et al in Rome, although there was no or poor relation between NO 2 and nonaccidental deaths, cardiovascular deaths and death from ischemic heart diseases in the crude analysis; there was a strong re Meanwhile, there was no relation between O 3 and cardio vascular mortality [36]. Chuang et al in a crosssectional study on 1023 elderly people in Taiwan reported that sys tolic and diastolic blood pressure had a strong, significant and positive correlation with the annual average level of O 3 [37]. But the study from Norway found no association between O 3 and blood pressure [38] and even a significant negative correlation was observed for O 3 in a multicenter study about the effects of air pollution on blood pressure in the Netherlands, Finland and Germany [39].…”
Section: Discussionmentioning
confidence: 95%
“…We are aware of only 3 relevant human studies examining the effect of long-term air pollutants exposure on prevalence of hypertension and arterial BP. 12,26,27 The results of these studies are inconsistent. In the Heinz Nixdorf Recall Study, a population-based prospective cohort in Germany, Fuks et al 27 investigated the cross-sectional association of residential long-term PM 2.5 and PM 10 exposure with arterial BP and hypertension on 4291 participants aged 45 to 75 years, taking short-term variations of PM and long-term road traffic noise exposure into account.…”
Section: Discussionmentioning
confidence: 99%